Effect of Nitrate and Sulfate on Atmospheric Corrosion of 304L and 316L Stainless Steels. Issue 4 (9th February 2017) - Cook, Angus J. M. C.; Padovani, Cristiano; Davenport, Alison J.
Abstract : The effects of nitrate and sulfate salts on the chloride-induced atmospheric pitting corrosion of 304L and 316L stainless steel was investigated through automated deposition of droplets of magnesium and calcium salts. Nitrate was found to inhibit pitting under magnesium salt droplets when the ratio between the deposition density of nitrate anions and chloride anions was above a critical value, which was the same for both 304L and 316L. This critical ratio was found to decrease with increasing humidity. Sulfate was also observed to inhibit pitting for MgCl2 + MgSO4 mixtures, but only at higher humidities. Sulfate did not show any inhibition for CaCl2 + CaSO4 mixtures, an effect attributed to the low solubility of CaSO4 . At low relative humidities, precipitation of the inhibiting salt was observed, leading in some cases to crevice-like corrosion under salt crystals. The pitting behavior was explained in terms of the thermodynamic behavior of concentrated solutions.